Efficiency of the silicate pump at a coastal oligotrophic site in the Mediterranean Sea - K. Leblanc; B. Quéguiner; P. Raimbault; N. Garcia (Biogeosciences, 2005)
A one-year survey of the sedimenting particulate material was conducted at the SOFi site located on the edge of the continental slope in the Gulf of Lions (Northwestern Mediterranean) between September 1999 and December 2000. The main focus of this paper was to establish an annual budget of biogenic silica export, to describe the seasonnal pattern of Si fluxes in relation to the organic and mineral C fluxes and to quantify the Si/C decoupling processes during sedimentation. The pattern of the downward flux of BSi was partly typical with increased daily sedimentation rates during spring followed by smaller peaks during summer. However, an unusual sedimentation event was recorded in the bottom trap in February before the spring thermal stratification occurred, and represented 37% of the annual BSi mass flux. The total annual BSi flux at the SOFi site was estimated from the bottom trap and amounted to 86.8 mmol Si m-2 y-1, while the organic carbon flux amounted to 154.9 mmol C m-2 y-1. The overall efficiency of C export to depth compared to surface primary production budgets was low (3%) and similar to values found for oligotrophic regions of the Eastern Mediterranean. On the other hand, we documented a very high efficiency of the Si export at the SOFi site, with 62% of the Si produced in the surface layer exported to the bottom trap. The excellent correlation between BSi and particulate organic C (POC) in the bottom trap further indicates that the bulk of the organic matter is transferred to depth in association with diatoms. However, the main fraction of the C produced by phytoplankton is lost in the water column through oxidation or metabolisation, while biogenic silica is more efficiently transferred to depth. This strong Si/C decoupling with depth is likely to be the cause of the spring depletion of silicic acid over the entire water column which was observed by mid-April in a companion study (Leblanc et al., 2003) and may cause a severe Si limitation of the diatom spring bloom in this oligotrophic region of the Gulf of Lions.